ESIPT-active multi-color aggregation-induced emission features of triphenylamine–salicylaldehyde-based unsymmetrical azine family. Issue 2 (6th December 2019) - Mathivanan, Moorthy; Tharmalingam, Balamurugan; Lin, Chia-Her; Pandiyan, Baskaran Vijaya; Thiagarajan, Viruthachalam; Murugesapandian, Balasubramanian
Abstract : A new family of ESIPT and AIE-active triphenylamine-appended unsymmetrical azine derivatives is reported. Abstract : The development of multi-color aggregation-induced emission (AIE)-featured azine molecules with excited-state intramolecular proton transfer (ESIPT) characteristics has drawn significant interest in recent years. In this study, we report the construction of donor-acceptor-structured triphenylamine-functionalized unsymmetrical azine molecules (L1 –L4 ) prepared from 4-(hydrazonomethyl)- N, N -diphenylaniline with different salicylaldehyde derivatives. By changing the electron donating ability at the ESIPT moiety, we could tune the optical properties of the newly synthesized molecules. All the compounds exhibited the AIE behavior in a THF/water mixture and the excited-state intramolecular proton transfer phenomenon. Further, the tuning of a peripheral substituent in the salicylaldehyde moiety resulted in different emission colors in the aggregated state. The crystal structure of all the compounds (L1 –L4 ) revealed that the multiple weak interactions present in the solid-state structure lead to various supramolecular networks. In addition, these molecules showed a prominent positive solvatochromic effect, which was confirmed by their solvent polarity-dependent emission behavior. The appearance of dual emission bands in the solid as well as in the solution state, lifetime values and HOMO, LUMO energy gap of the keto and enol forms strongly support the occurrence of ESIPT in all the compounds (L1 –L4 ). Furthermore, the presence of two different electron donating groups in L3 (triphenylamine and diethylamino) induced pH-dependent emissive features in solution.